Why Standard Measures of Human Capital are Misleading - Eric A. Hanushek (14185, 2015)
of measurement issues surrounding the concept of human capital. The traditional approach of rely entirely on measures of school attainment, while convenient, is almost certainly misleading. The availability of cognitive skills measures greatly improves on